Tsunami Exercises on a Remote Basis: Costa Rican experiences - Chacon-Barrantes, Silvia (2021)
As part of the guidelines to obtain the Tsunami Ready recognition from IOC/ UNESCO, the Pacific communities of Tamarindo and Uvita were required to perform a tsunami exercise. On the 16 March 2020 started in Costa Rica the lockdown because of the SARS-Cov2 virus. The measures correspond- ing to the lockdown have alternatively relaxed and tightened since then, but have implied telework for the University staff and the suspension of domestic trips. The National Emergency Commission (CNE), the Costa Rica disaster management office, suspended all gatherings that were not strictly necessary. Therefore, the tsunami exercises planned for both Tamarindo and Uvita were suspended. Despite all these limitations, it was possible to carry out remote table-top tsunami exercises with both communities, with representatives from SINAMOT participating in the video calls. In Tamarindo, the Community Emergency Committee (CCE in Spanish) met at a hotel in separate rooms, in this way the CCE was able to better control the exercise. In Uvita, each partici- pant was in a separate location, from where they participated in a group video call as well as individual telephone calls. Having the table-top exercises on a remote basis had some advantages: 1. it represented a more realistic scenario where the participants were not in the same room and had to make decisions on a remote basis. 2. It generated a better evaluation of the message dissemi- nated within the participants and of the technological capacities of the CCE in case of emergency. 3. It simplified the evaluation process, as all the mes- sages were recorded. Theoretically, the exercises completed the guidelines for both communities to become Tsunami Ready. However, Costa Rica National Tsunami Ready Board hasn’t been able to meet, as authorities from CNE belonging to this board are completely devoted to the sanitary emergency.